PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI BUMIKU SAYANG, BUMIKU MALANG SISWA KELAS V SDN 2 LAMCOT - Siti Ayu Rahmina; Ahmad Nasriadi; Dzikrul Rizki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing the Problem Based Learning (PBL) model on students' critical thinking skills on the topic "Bumiku Sayang, Bumiku Malang" in the fifth grade of SDN 2 Lamcot. This research used a quantitative approach with a Pre-Experimental Design in the form of One Group Pretest-Posttest Design. The population consisted of all 23 fifth-grade students, all of whom were selected as the sample using saturated sampling technique. Data collection techniques included observation, tests, and documentation, with instruments consisting of observation sheets and essay tests. Data were analyzed using a paired sample t-test. The results showed a significant improvement: pretest mean was 63.91 and posttest mean was 82.61, with an N-Gain value of 0.52 (moderate category). The t-test result showed t-count (18.41) > t-table (2.07) at significance level 0.05 (dk = 22), leading to rejection of H₀ and acceptance of H₁. Therefore, the implementation of the Problem Based Learning model significantly improves the critical thinking skills of fifth-grade students at SDN 2 Lamcot on the topic "Bumiku Sayang, Bumiku Malang."